1981
DOI: 10.1210/jcem-52-1-116
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Metabolites and Calcium Metabolism in Patients with Nephrotic Syndrome and Normal Renal Function*

Abstract: Patients with nephrotic syndrome (NS) lose 25-hydroxyvitamin D3 (25OHD3) in the urine and have low blood levels of this metabolite. This abnormality may be responsible for the hypocalcemia, i.e. low ionized calcium. The mechanism of the hypocalcemia is not evident. It is possible that the low value of 25OHD results in low blood levels of other vitamin D metabolites, such as 1,25-dihydroxyvitamin D [1,25-(OH)2D] and 24,25-(OH)2D3; a deficiency of these compounds may cause defective intestinal absorption of calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 19 publications
5
60
0
1
Order By: Relevance
“…In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22). Likewise, total 1,25(OH) 2 D levels have been found to have decreased (12,21,23,24) or to have been unchanged (22,25) in patients with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22). Likewise, total 1,25(OH) 2 D levels have been found to have decreased (12,21,23,24) or to have been unchanged (22,25) in patients with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with liver disease (16-18) and the nephrotic syndrome (19,20) have DBP levels that are lower than normal. Low 1,25(OH)2D concentrations have been reported in these conditions by some investigators (21,22) but not by others (23,24). If levels are indeed lower, this circumstance may be caused by a reduction in the amount of 1,25(OH)2D bound to DBP, although abnormalities in hepatic or renal metabolism of vitamin D in such patients may be partially responsible.…”
Section: Introductionmentioning
confidence: 90%
“…A lthough most patients with idiopathic nephrotic syndrome (NS) present with normal GFR, alterations of mineral homeostasis similar to those encountered with chronic renal failure are frequently identified, including hypocalcemia, reduced serum vitamin D metabolites, and elevated levels of immunoreactive parathyroid hormone (PTH) (1)(2)(3)(4)(5)(6). Metabolic balance studies have demonstrated intestinal malabsorption of calcium (5) as well as excessive urinary losses of various vitamin D metabolites and their binding proteins (2,7).…”
mentioning
confidence: 99%
“…Serum phosphorus concentration is usually normal (1,3,5), calcitriol remains normal in most patients (3,15), and despite low serum levels of ionized calcium, PTH levels are not consistently elevated (1,3,5,6,15). Thus, the mechanisms that result in altered BMD and bone histology in patients with NS before the reduction in GFR are still unclear.…”
mentioning
confidence: 99%